Type 2 diabetes therapeutic strategies: why don't we see the «ELEPHANT» in the room? - Shmuel Levit (Endocrinology Research Centre, 2016)
During the past two decades, the unequivocally recommended treatment method of Type 2 diabetes mellitus was insulin administration and intensification in the earliest possible stage of the diagnosis. This approach is not only unfounded but was never scientifically proven. Yet, it has been zealously advocated to medical professionals. In fact, a sound body of evidence disproves this long-standing treatment approach. This method is a cornerstone of, what we now know to be two great illusions of past century, namely, glucocentrism and intensification. Numerous recently published studies provide alarming data regarding serious side effects of blind intensification and insulin overdosing in T2DM. They raise major concerns and call for revision of the traditional approach. Since insulin is an integral and deeply rooted part of the intensification agenda of treating T2DM, it has now suffered a serious drawback. Alternatively, in this review authors present the novel Gravicentric (Energy) concept of T2DM acceptance and therapy. They offer a new classification of anti-diabetes drugs based on their energy effect and present their Gravicentric Algorithm for wide practical utilization. For that reason, the "ELEPHANT" abbreviation was found as a helpful reminder. Viewing T2DM as disease of energy balance together with anti – energy drugs implementation provide medical doctors an unique opportunity to transform T2DM from "slowly – progressive" disease to rapidly reversible condition, which it actually is.